A Novel Electrochemically Switchable Conductive Polymer Interface for Controlled Capture and Release of Chemical and Biological Entities. Issue 13 (20th March 2022) - Akbarinejad, Alireza; Hisey, Colin Lee; Martinez‐Calderón, Miguel; Low, Jeffery; Bryant, Devon T.; Zhu, Bicheng; Brewster, Diane; Chan, Eddie Wai Chi; Ashraf, Jesna; Wan, Ziyao; Artuyants, Anastasiia; Blenkiron, Cherie; et al.
Abstract: Materials platforms that enable controlled isolation and subsequent release of chemical/biological entities are in great demand for a diverse range of practical applications. Current technologies lack good control and efficiency of the release, which is needed to preserve the captured targets of interest. Here, this need is addressed by providing a versatile, controllable, electrochemical capture/release interface. The interface consists of a highly porous electrospun membrane, electrodeposited with a thiol‐functionalized 3, 4‐ethylenedioxythiophene (EDOT) conductive terpolymer, in which the thiol moiety undergoes oxidation/reduction cycles at moderate potentials (+1.0 and −0.8 V, respectively) to enable capture/release. The fast oxidative capture (1 min) and reductive release (2 min) of a model thiol molecule in a highly controllable manner, followed by successful capture/release of an antibody, are demonstrated. Then, femtosecond laser‐patterning is used to fabricate an array of ≈30 µm pores on the electrospun membrane, subsequently coated with the conducting terpolymer, enabling the highly efficient (>90%), fast (20 min) and selective capture of MCF7 cancer cells with 33% release efficiency when polarized at −0.8 V. The released cells show a high level of viability, indicating the capture and release process does not affect cell survival. Abstract : A novel electrochemically switchable, functionalized conductive terpolymer is designed and conjugated to a highly porous and biocompatible electrospun membrane for selective capture and release of chemical and biological entities. The capture and release mechanism is through the redox formation (at +1.0 V vs Ag/AgCl) and cleavage (at −0.8 V vs Ag/AgCl) of a disulfide covalent bond in the terpolymer structure.